1981
DOI: 10.2105/ajph.71.2.132
|View full text |Cite
|
Sign up to set email alerts
|

Polychlorinated biphenyl contamination of nursing mothers' milk in Michigan.

Abstract: The problem of environmental contamination by toxic substances and human exposure to these substances has attracted increased attention

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

1983
1983
2000
2000

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(12 citation statements)
references
References 30 publications
1
11
0
Order By: Relevance
“…Children of farm and migrant workers could be From Jacobson et al ( 1989 ) and Kuwabara et al ( 1978 ) . Similar findings were reported by Yakushiji et al ( 1984 ) , Eyster et al ( 1983 ) , Wolff ( 1983 ) , Mes et al ( 1984 ) , Wickizer et al ( 1981 ) and Niessen et al ( 1984 ) . Wolff et al ( 1982 ) .…”
Section: Pesticidessupporting
confidence: 90%
“…Children of farm and migrant workers could be From Jacobson et al ( 1989 ) and Kuwabara et al ( 1978 ) . Similar findings were reported by Yakushiji et al ( 1984 ) , Eyster et al ( 1983 ) , Wolff ( 1983 ) , Mes et al ( 1984 ) , Wickizer et al ( 1981 ) and Niessen et al ( 1984 ) . Wolff et al ( 1982 ) .…”
Section: Pesticidessupporting
confidence: 90%
“…In one of the studies, a variety offactors that might affect PCB blood levels were examined, and it was found that age, sex, and amount of fish consumption (in that order) were the most important (60). PCBs can also be passed from mother to infant through the placenta or breast milk (59,61,62). It seems to be well established that higher exposure to PCBs means a higher blood level of PCBs.…”
Section: Strategy Of Biological Markers: a Measure Of Internal Dosementioning
confidence: 99%
“…Certain couples may wish to obtain information regarding the possible adverse effect of PCBs or dioxins and furans on reproductive outcome and plan future child bearing accordingly. In a related matter, because PCBs and related compounds concentrate in breast milk (as well as pass through the human placenta) questions of breast feeding by the exposed mother arise (26)(27)(28)(29) One question the occupational medicine physician is asked frequently by exposed workers and their families is whether the compounds can be removed from the body, especially if they are found by direct measurement in fat or blood, or indirect measures of exposure and sensitivity, such as elevated liver enzymes or skin changes, etc., to be in the exposed worker.…”
Section: Treatment Of Patientsmentioning
confidence: 99%